2011
DOI: 10.2147/dmso.s16175
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between fat deposition in the liver and skeletal muscle and insulin sensitivity in Japanese individuals: a pilot study

Abstract: Purpose:To evaluate the relationships between insulin sensitivity (IS), body fat accumulation, and aerobic capacity in middle- to older-aged Japanese participants with visceral adiposity.Participants and methods:Aerobic capacity was measured during an incremental ramp exercise test. Computed tomography was used to measure visceral (VFA) and subcutaneous (SFA) fat area, the fat in liver-to-spleen ratio (L/S), and low-density skeletal muscle area (LDMA). IS was assessed using euglycemic-hyperinsulinemic clamps.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
(58 reference statements)
0
10
1
Order By: Relevance
“…( 29 ) Ectopic fat accumulation, which has a close association with visceral adiposity, is reported to be strongly correlated with insulin resistance. ( 30 ) Unfortunately, we did not have data of the presence of NAFLD in this study population. Thus, the concept of metabolically abnormal or presence of NAFLD is almost same as presence of abdominal obesity.…”
Section: Discussionmentioning
confidence: 96%
“…( 29 ) Ectopic fat accumulation, which has a close association with visceral adiposity, is reported to be strongly correlated with insulin resistance. ( 30 ) Unfortunately, we did not have data of the presence of NAFLD in this study population. Thus, the concept of metabolically abnormal or presence of NAFLD is almost same as presence of abdominal obesity.…”
Section: Discussionmentioning
confidence: 96%
“…As we known, increased regional lipid content in the liver and muscle are associated with insulin resistance [15,16]. NC is not only associated with obesity and regional fat distribution, but also can be used for clinical screening of insulin resistance in high risk populations [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Excess weight is a well‐known risk factor for type 2 diabetes mellitus (T2DM), albeit the precise mechanisms linking these conditions have not been fully elucidated. Aside from still largely unexplored genetic predispositions, studies have identified possible connections between weight gain and T2DM which involve unfavourable visceral fat deposition (particularly in the liver, pancreas and skeletal muscles) , increased production of proinflammatory cytokines by the adipose tissue , abnormal fatty acid metabolism , reduced levels of adiponectin and cellular processes such as mitochondrial dysfunction and endoplasmic reticulum stress .…”
Section: Introductionmentioning
confidence: 99%